Comparative mitogenomic and phylogenetic insights from four newly sequenced tick mitochondrial genomes - Liu, Shuang; Hou, Rui; Zhang, Quanfu; Duan, Mingna; Tang, Shaobo; Wang, Weishuo; Chen, Jiayao; Wu, Jun; Shen, Yujuan; Gu, Wei; Sun, Yi; Yang, Xing (Frontiers in Veterinary Science, 2026)
Ticks, recognized as the second most significant vector of pathogens after mosquitoes, are of considerable interest in medical research. Although mitochondrial genomes are commonly employed in the phylogenetic studies of insects and arthropods, investigations into tick mitochondrial genomes are relatively scarce. The evolutionary and phylogenetic relationships at the family and genus levels remain unresolved. In this study, the mitochondrial genomes of Haemaphysalis warburtoni, Ixodes crenulatus, Rhipicephalus bursa, and Rhipicephalus pumilio were first sequenced and annotated based on the Illumina NovaSeq 6,000 platform, and compared with the mitochondrial genes of 150 other hard ticks. All examined tick mitochondrial genomes exhibit a notable AT bias, with A+T content ranging significantly from 72.28% to 81.06%. They also exhibit distinct codon usage patterns, with most codons ending in either A or U. A phylogenetic analysis, based on 13 protein-coding genes (PCGs), confirms that the Ixodidae family forms a monophyletic group. Based on the phylogenetic analysis of 13 protein-coding genes, the relationships of Ixodidae family as follows: Ixodes + (Robertsicus + ((Bothriocroton + Archaeocroton + Cryptocroton + Haemaphysalis) + (Amblyomma + (Dermacentor + (Rhipicentor + (Hyalomma + Rhipicephalus)))))). This study provides in-depth insights into tick mitochondrial genomes, offering important references for research on their systematics, evolution, and species identification, while also laying the groundwork for tick-borne disease control and public health risk assessment.